Larangan Merokok di Mata Mahasiswa: Studi Tentang Kebijakan Larangan Merokok di Tempat Umum - Fadhil Ilhamsyah; Afrizal Tjoetra; Ikhsan Ikhsan (Jurnal Public Policy, 2020)
This paper explains about Teuku Umar University Students' perceptions of the smoking ban policy at public places in West Aceh Regency. The smoking ban policy is an effective way of controlling smoking and indirectly reduces the negative impact on the health of passive smokers due to smoking by releasing it in public places. This research uses quantitative research methods with survey methods. the population of Teku Umar University students who accept 50 people who have an age range between 18-25 years and are male and female. The results showed that most Teuku Umar Universities were of the view that the ban on smoking in public places had run well. Even so, there are still students who do not need this policy, this can be seen from the habits of students who smoke in places that include smoking areas